Adenovirus-delivered GFP-HO-1C[INCREMENT]23 attenuates blood–spinal cord barrier permeability after rat spinal cord contusion. Issue 5 (21st March 2018) - Chang, Sheng; Bi, Yunlong; Meng, Xiangwei; Qu, Lin; Cao, Yang
Abstract : The blood–spinal cord barrier (BSCB) plays a key role in maintaining the microenvironment and is primarily composed of tight junction proteins and nonfenestrated capillary endothelial cells. After injury, BSCB damage results in increasing capillary permeability and release of inflammatory factors. Recent studies have reported that haem oxygenase-1 (HO-1) fragments lacking 23 amino acids at the C-terminus (HO-1C[INCREMENT] 23) exert novel anti-inflammatory and antioxidative effects in vitro . However, no study has identified the role of HO-1C[INCREMENT] 23 in vivo . We aimed to investigate the protective effects of HO-1C[INCREMENT] 23 on the BSCB after spinal cord injury (SCI) in a rat model. Here, adenoviral HO-1C[INCREMENT]23 (Ad-GFP-HO-1C[INCREMENT]23) was intrathecally injected into the 10th thoracic spinal cord segment (T10) 7 days before SCI. In addition, nuclear and cytoplasmic extraction and immunofluorescence staining of HO-1 were used to examine the effect of Ad-GFP-HO-1C[INCREMENT]23 on HO-1 nuclear translocation. Evan's blue staining served as an index of capillary permeability and was detected by fluorescence microscopy at 633 nm. Western blotting was also performed to detect tight junction protein expression. The Basso, Beattie and Bresnahan score was used to evaluate kinematic functional recovery through the 28th day after SCI. In this study, the Ad-GFP-HO-1C[INCREMENT]23 group showed better kinematic functional recovery after SCI than the Ad-GFP and Vehicle groups, as well as smaller reductions in TJ proteins and capillary permeability compared with those in the Ad-GFP and Vehicle groups. These findings indicated that Ad-GFP-HO-1C[INCREMENT]23 might have a potential therapeutic effect that is mediated by its protection of BSCB integrity.